2023
DOI: 10.1108/ijoem-02-2022-0200
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment, technological transfer, employment generation and economic growth: new evidence from Ghana

William Obeng-Amponsah,
Erasmus Owusu

Abstract: PurposeThis study examines the effect of foreign direct investment (FDI) on employment and economic growth in Ghana and examines the role of technology in these relationships.Design/methodology/approachThis study applied the autoregressive distributed lag (ARDL) bounds testing approach to cointegration and Granger causality tests to data from 1995 to 2017.FindingsBased on the empirical analysis, the key findings are as follows: FDI does not affect economic growth or employment in Ghana. However, technology mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Hence, the technological diffusion of the financial sector and improvement in the quality of financial services will attract foreign and local investments and improve the industrial sector since it leads to easy fund transfer from the finance sector to the real sector (Obeng-Amponsah & Owusu, 2023). Moreover, within the Solow growth model and Evolutionary Institutional theory framework, the Endogenous Growth model asserts that technology plays a pivotal role in economic growth, exerting a substantial influence on the promotion of overall economic development.…”
Section: Short Run and Long Run Estimationsmentioning
confidence: 99%
“…Hence, the technological diffusion of the financial sector and improvement in the quality of financial services will attract foreign and local investments and improve the industrial sector since it leads to easy fund transfer from the finance sector to the real sector (Obeng-Amponsah & Owusu, 2023). Moreover, within the Solow growth model and Evolutionary Institutional theory framework, the Endogenous Growth model asserts that technology plays a pivotal role in economic growth, exerting a substantial influence on the promotion of overall economic development.…”
Section: Short Run and Long Run Estimationsmentioning
confidence: 99%
“…Gunby obtained no significant evidence of positive spillovers from FDI at the aggregate level of China's economy using a meta-analysis [23]. Obeng-Amponsah examined data for Ghana from 1995 to 2017 and found that FDI does not affect economic growth or employment in Ghana [24].…”
Section: Introductionmentioning
confidence: 99%